Norsk krigsfilm og det erindringsteoretiske perspektiv: Tilfellet Kalde spor - Tonje Haugland Sørensen (Norsk Medietidsskrift, 2011)
Abstract Norwegian war films have been defined colloquially as too heroic and lacking in nuance in their depiction of the Second World War. However, a survey of the films, usually referred to as occupation dramas, reveals that several deal with questions of trauma, doubt and regret. With a basis in the theoretical ideas of Cultural Memory and Remembrance, this paper focuses on one of these unheroic films – Arne Skouens Kalde Spor (1962) – and shows the various ways that the legacy of the war can be questioned and problematised. Furthermore, the paper strives to show the internal problematisation within the occupation drama genre as related to depictions of the Second World War.